Retorika Etos Patos Logos dalam Ceramah Ustadz Hanan Attaki Tentang Mengingat Kematian - Nur Syavika; Rhani Febria (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to identify, describe, and dismantle in depth the utilization of rhetorical elements namely ethos (credibility), pathos (emotional appeal), and logos (logical reasoning) applied by Ustadz Hanan Attaki in his lecture on the importance of remembering death. The methodological foundation relies on a qualitative approach using qualitative content analysis to interpret the meanings, symbols, and rhetorical weight contained within the lecture text. Data collection was carried out through library research by reviewing relevant scientific literature and compiling a verbatim transcript from the video "Mengingat Kematian (Sharing Ramadhan)" on a digital platform as the primary source. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing to ensure objective and theoretically grounded findings. The results of the analysis demonstrate that Ustadz Hanan Attaki harmoniously and effectively integrates the three rhetorical pillars to construct a highly persuasive da'wah message for the younger generation. Ethos is established through practical wisdom (phronesis) by textually mastering religious proofs, moral virtue (arete) using inclusive and egalitarian language, and goodwill (eunoia) through deep empathy toward human negligence. Pathos is strategically managed by flipping the scary stereotype of death into a gentle medium for softening the heart, utilizing calculated fear appeals regarding sudden mortality, and presenting beautiful emotional comfort about the peaceful nature of the barzakh realm. Logos is systematically reconstructed using deductive reasoning based on sacred texts, clear causal relationships regarding the function of remembering death, categorical syllogisms on the urgency of immediate repentance, and inductive empirical proof from global events. This comprehensive rhetorical synergy successfully transforms a heavy, eschatological topic into an accessible, logical, and deeply touching spiritual reflection that motivates immediate behavioral reform.